2018
DOI: 10.1007/s00192-018-3682-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk for stress urinary incontinence in women with postmenopausal hormone therapy

Abstract: The use of HT regimens may predispose to the de novo development or worsening of pre-existing SUI. Thus, caution is needed when these regimens are prescribed to women with mild stress-related urine leakage or with established SUI risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…In the literature, there are studies reporting that menopause has no effect on UI (16). However, some studies also report a negative relationship between menopausal status and UI (25). According to the results of our study, there were significant differences in terms of ICIQ-SF scores with 317 (50.9%) participants who did not enter menopause and those with a menopause duration of 5 years or more.…”
Section: Discussionsupporting
confidence: 43%
“…In the literature, there are studies reporting that menopause has no effect on UI (16). However, some studies also report a negative relationship between menopausal status and UI (25). According to the results of our study, there were significant differences in terms of ICIQ-SF scores with 317 (50.9%) participants who did not enter menopause and those with a menopause duration of 5 years or more.…”
Section: Discussionsupporting
confidence: 43%
“…Other risks associated with MHT include dementia (in women aged ≥ 60 years) [99], gallbladder disease [100], and urinary incontinence [101].…”
Section: Safety Aspects Of Menopausal Hormone Therapymentioning
confidence: 99%
“…HRT was long being used as a therapeutic option for treating UI plus symptoms of vulvovaginal atrophy until the results of a systematic review revealed that systemic HRT increases the risk of UI [24], while vaginal estrogen improves this process [26]. An extensive case-control study was conducted in Finland from 1994 to 2011 to investigate the conflicting effects of the topical and systemic forms of estrogen, and the results obtained showed that both topical and systemic forms of hormone therapy exacerbate SUI symptoms [27]. Invasive and surgical measures are considered when conservative management and medication prove ineffective in treating UI [28].…”
Section: Discussionmentioning
confidence: 99%